Asset Security and User Satisfaction Drive Public Asset Value in Indonesia - Syamsul Risal; Rahmawati; Muammar Khaddapi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the determinants of public asset value in local government, focusing on the roles of asset inventory, maintenance, and security, with user satisfaction as a mediating variable. The research addresses how these asset management practices influence public asset value directly and indirectly through user satisfaction. A quantitative explanatory design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through a structured Likert-scale questionnaire from 30 respondents involved in asset management across multiple government agencies. The analysis included evaluation of measurement and structural models, as well as mediation testing bootstrapping. The results show that asset security has a positive and significant effect on both user satisfaction and public asset value, while asset inventory significantly influences user satisfaction but not asset value directly. Asset maintenance does not exhibit a significant effect on either variable. User satisfaction significantly affects public asset value and mediates the relationships between asset inventory and security with asset value. These findings indicate that public asset value is driven more by perceived usability and security than by administrative or routine maintenance processes. The study contributes to theory by integrating technical and user-centered perspectives in asset management and offers practical implications for policymakers to prioritize asset security and user-oriented strategies to enhance the effectiveness and value of public assets.